Frontline employees in the health clinic: Impression management multiplexing when performing in-the-round. Issue 3 (3rd July 2018) - Harrison, Millie A.; Smith, William Roth; Greenwell, Mackenzie R.; Stephens, Keri K.
ABSTRACT: Using Goffman's dramaturgical perspective of impression management, the present study focuses on the staged performances of frontline employees (FLEs) at a Federally Qualified Health Center (FQHC). Qualitative analysis reveals how FLEs in health clinics engage in staged communication to perform their jobs and facilitate patient care. Our findings highlight three overarching themes in which FLEs' communication compounds frontstage and backstage practices: performing on a multidimensional stage, enacting scripted and improvisational roles, and incorporating regulatory strategies to accomplish their work. We argue these communicative practices culminate into the proposed theoretical concept of impression management multiplexing (IMM) . Implications for clinic FLEs, patient care, and patient privacy are discussed.